Answer:
-4
Step-by-step explanation:
Rewrite 16 as 4 squared
Pull terms out from under the radical, assuming positive real numbers
-1 x 4
Then you get the answer -4
2 x (3+6z) = 6 +12z
This is how you do it
All of these sets meet the requirements of the triangle inequality. The sum of any two numbers in the set is greater than the third one. (You really only need to check that the sum of the smallest two is greater than the largest.)
It can help to resolve the numbers that are only indicated as to value.
√13 ≈ 3.606
2√10 ≈ 6.325
_____
Your comparisons can be ...
2 + 3 = 5 > 3.606 . . . is a triangle
5 + 5 = 10 > 6.325 . . . . . . is a triangle
5 + 12 = 17 > 15 . . . . . . . . is a triangle
Answer:
Step-by-step explanation:
3-(2x-5)=-4(x+2)
We simplify the equation to the form, which is simple to understand
3-(2x-5)=-4(x+2)
Remove unnecessary parentheses
3-2x+5=-4*(x+2)
Reorder the terms in parentheses
3-2x+5=+(-4x-8)
Remove unnecessary parentheses
+3-2x+5=-4x-8
We move all terms containing x to the left and all other terms to the right.
-2x+4x=-8-3-5
We simplify left and right side of the equation.
+2x=-16
We divide both sides of the equation by 2 to get x.
x=-8
Answer:
a=7
Step-by-step explanation:
24^2+a^2=25^2
576+a^2=625
49=a^2
a=7